The Relationship between Knowledge and Attitudes about Community Disaster Preparedness in Lambung Village, Banda Aceh - Taufik Suryadi; Zulfan Zulfan; Kulsum Kulsum (International Journal of Disaster Management, 2021)
Disaster preparedness is an important component that all levels of society must address in terms of disaster management. Lack of knowledge on disaster preparedness will have a direct impact on one's attitude in responding to disasters. This study aims to determine the relationship between community knowledge and disaster preparedness attitudes in the Lambung village, Banda Aceh. This type of research is analytic observational with a cross sectional approach. The samples in this study were the people of the Lambung village of Banda Aceh City with a sample of 100 people. The data was collected using a questionnaire that has been tested for its validity and reliability. Data analysis was performed univariate and bivariate using the chi-square test. The results showed that the people of Lambung village had a fairly good knowledge of disaster preparedness with levels from high to low being moderate (63.0%) and good (37.0%). The attitude of the students showed that the highest percentage was moderate (69.0%) and well followed (31.0%) in terms of disaster preparedness. The chi-square test results showed that there was a significant relationship between public knowledge and disaster preparedness attitudes about disaster preparedness (p = 0.001). The conclusion of this study is that there is a relationship between public knowledge and disaster preparedness attitudes in Lambung Village, Banda Aceh. This study recommends the importance of preparedness in the community so that the risk of the large number of victims due to disasters can be reduced.